2021
DOI: 10.1177/13524585211011450
|View full text |Cite
|
Sign up to set email alerts
|

Optic chiasm involvement in AQP-4 antibody–positive NMO and MOG antibody–associated disorder

Abstract: Background: Optic neuritis (ON) is often the presenting symptom in inflammatory central nervous system demyelinating disorders. Objective: To compare the frequency and pattern of optic chiasm involvement in patients with aquaporin-4-immunoglobulin G (AQP4-IgG)-associated ON to patients with myelin oligodendrocyte glycoprotein-immunoglobulin G (MOG-IgG)-associated ON. Methods: Retrospective review of all patients evaluated at Mayo Clinic, Stanford University and Ramathibodi Hospital who were found to have: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 11 publications
(20 reference statements)
3
35
2
Order By: Relevance
“…Previous studies [19][20][21][22][23]30] reported posterior lesions in between 35% and 80% of the studied cases. Furthermore, longitudinally extensive optic nerve involvement was reported in 13%-100% [19][20][21][22][23] of NMOSD-ON patients.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies [19][20][21][22][23]30] reported posterior lesions in between 35% and 80% of the studied cases. Furthermore, longitudinally extensive optic nerve involvement was reported in 13%-100% [19][20][21][22][23] of NMOSD-ON patients.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, MRI is crucial to exclude differential diagnoses as well as for the evaluation of inflammatory lesions during follow-up [17]. While brain MRI lesions in both NMOSD and MOGAD have been described [9][10][11][12][13][14][15][16][17][18], only a few previous studies have evaluated the radiological features of NMOSD-ON versus MOGAD-ON, focusing on optic chiasm involvement [19][20][21][22][23].…”
Section: Although Conventional Brain Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation
“…97 In the brain, there can be poorly demarcated "fluffy" deep white matter, juxtacortical, brainstem or cerebellar peduncle lesions. 38,61,62 A recent study by Tajfirouz et al 98 comparing 74 NMOSD and 80 MOGAD patients reported chiasmal involvement in 20% and 16% respectively (P ¼ 0.66). Chiasmal involvement in MOGAD was also more likely to be part of a longitudinally extensive optic nerve lesion.…”
Section: Clinical and Imaging Characteristicsmentioning
confidence: 95%
“…In MOGAD, long lesions have a tendency to affect the anterior segment of the nerve and co-occur with optic nerve swelling on fundoscopy, while AQP4-Ab optic neuritis has a predilection for posterior segments and the optic chiasm [40,44]. Optic chiasm lesions also occur in MOGAD where they are usually a part of the longitudinally extensive involvement of the whole nerve starting www.journals.viamedica.pl/neurologia_neurochirurgia_polska in the orbit [46]. Longitudinally extensive lesions of the optic nerve are rare in MS [47,48].…”
Section: Optic Nerve Imagingmentioning
confidence: 99%